Eye of the Whale: Epic Passage From Baja To Siberia - Russell Dick (Island Press, 2004)
More than a century ago, the whaler Charles Melville Scammon chased pods of gray whales across the Pacific, slaughtering them by the hundreds and driving them nearly to the point of extinction. Dick Russell, a noted conservationist and journalist, follows Scammon's wake, bringing news both good and bad about the condition of the gray whale today.